Exploring brain changes in self-reported anxiety: Cutting-edge exploratory diffusion tensor imaging study reveals distinct alterations in white matter tract structure among non-clinical individuals - Wan Adibah Nadiah, Abd Razak; Rajeev Shamsuddin, Perisamy; Che Mohd Nasril, Che Mohd Nassir; Muzaimi, Mustapha; Mohd Khairul Izamil, Zolkefley (Universiti Sultan Zainal Abidin, 2025)
Previous research utilising diffusion tensor imaging (DTI) has reported disruptions in white matter pathways among individuals with anxiety-related disorders. However, there is limited research focusing on healthy or non-clinical groups with self-reported anxiety symptoms. This investigation aims to explore how self- reported anxiety relates to white matter microstructural differences in non-clinical adult brains. A total of twenty-nine participants took part in the study. Each participant completed the Depression Anxiety Stress Scale-21 (DASS-21) and underwent a detailed high-resolution 3T magnetic resonance imaging (MRI). Diffusion MRI connectometry was conducted to generate correlational tractography, identifying links between generalised fractional anisotropy (FA) values of white matter and anxiety scores derived from the DASS-21. The average anxiety score, as measured by the DASS-21, was 10.97 with a standard deviation of 7.002. Notably, a significant inverse association emerged between anxiety levels and FA values in several white matter regions, including the left and right inferior fronto-occipital fasciculi, the left inferior longitudinal fasciculus, the right superior longitudinal fasciculus, and the left parahippocampal cingulum bundle (p < 0.05). The local brain connectome associated with anxiety may serve as a biomarker for early diagnosis and prevention of anxiety disorders in non-clinical populations.